Leadership Style Visionary-Transformational Ayep Zaki in the Realization of the Vision of "Faith" in the City of Sukabumi - Alif Hady Saputra; Nenden Nenden; Aqila Zayyan; Utari Sari Safrina; Andra Septiansyah (Majapahit Journal of Islamic Finance and Management, 2025)
This study examines the leadership style of H. Ayep Zaki, Mayor of Sukabumi (2025 – 2030), in translating his “IMAN” vision (Innovative, Self-Reliant, Religious, Nationalistic) into 19 flagship programs promised during the 2024 mayoral election. Using a qualitative descriptive approach based on literature and document review, the article explores his visionary–transformational leadership features, implementation strategies, first-100-day achievements, and public critiques. Findings reveal that a blend of visionary, participative leadership and public-service orientation accelerated the launch of the RT endowment fund, doubled RT/RW incentives, awarded 100 scholarships per sub-district, and expanded digital public services (“Sukabumi Menyala”). Nevertheless, legislative pushback on the municipal waqf endowment and delays in finalizing the Mid-Term Development Plan (RPJMD) pose major challenges. The study underlines the need for multi-stakeholder collaboration and participatory governance to ensure program sustainability.